INSTITUSI MEDIA MASSA DAN PENGARUHNYA TERHADAP MASYARAKAT - Abdul Pirol (IAIN Palopo, 2009)
The concept of institution in media studies sometimes overlapp with industrys concept. The concept of institution is related to the ideas taken from sociology, psychology, and politics. Therefore, the aspects of media activity organization is more difficult to understand, because it is related to the procsess and the hidden relationship, rather than, the balance paper of company or work contracts. This paper purposes to show that institution aspect and industry of a media need to be analyzed and understood well. Before conducting the media analysis in more detail from all of its sides. The literature study of institution and industry theories are expected to fulfill such on expectation. Media institution is related to organization aspect from one media. In this aspect it explains the things which are related to organization structure, corporation, motivation and professionalism. While, media industry is related to bussiness function, which its reference more at is profit and loss that can be gained in delivering information. Absolutely, further analysis on media closely related to ethics.